Autologous Fat Grafting as a Novel Antiestrogen Vehicle for the Treatment of Breast Cancer. Issue 3 (September 2017) - Thomas, Scott; Chen, Stephanie; Sbitany, Hani; Kwon, Edwin; Piper, Merisa; Park, Jeenah; Terranova Barberio, Manuela; Pawlowska, Nela; Munster, Pamela N.
Abstract : Background: Adipose fat transfer is increasingly used for contour corrections of the tumor bed after lumpectomy and breast reconstructions after mastectomy. The lipophilic nature of the fat tissue may render adipocytes an ideal vehicle with which to deliver a high boost of an antiestrogen to the tumor bed to serve as an adjunct systemic hormonal therapy. The authors therefore tested whether adipocytes could safely be loaded with an antiestrogen and allow for release at therapeutic concentrations to treat breast cancer. Methods: Adipose tissue was collected from patients undergoing autologous fat grafting. The influence of adipose tissue on tumorigenesis was determined both in vitro and in vivo using breast cancer cell lines. Ex vivo, adipose tissue was assessed for its ability to depot fulvestrant and inhibit the growth of breast cancer cell lines. Results: Adipose tissue harvested from patients did not promote breast cancer cell growth in vitro or in an in vivo mouse model. Adipose tissue was successfully loaded with fulvestrant and released at levels sufficient to inhibit estrogen receptor signaling and growth of breast cancer cells. Conclusions: This work supports the hypothesis that adipose tissue used for autologous fat grafting can serve as a novel method for local drug delivery. As this technique is used to reconstruct a variety of postsurgical defects following cancer resection, this approach for local drug delivery may be an effective alternative in therapeutic settings beyond breast cancer.